2019
DOI: 10.1080/00220388.2019.1640871
|View full text |Cite
|
Sign up to set email alerts
|

Does Non-farm Income Affect Food Security? Evidence from India

Abstract: Livelihood diversification and greater non-farm income have been considered as useful mechanisms to propel growth, lower rural poverty and augment farm income in the developing countries. Little, however, is known about its im-plications for nutritional outcomes such as dietary diversity. This article con-tributes to the literature by investigating whether greater non-farm income helps in improving food consumption patterns and dietary diversity. Using a nationally representative panel data of rural India and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 53 publications
3
35
0
Order By: Relevance
“…Bezu et al (2012); Scharf and Rahut (2014) have also found that non-farm employment increases household expenditure in rural Ethiopia. These results also indirectly support empirical findings on the impact of non-farm employment on food security (Babatunde and Qaim, 2010;Imai et al, 2015;Tsiboe et al, 2016;Dzanku, 2019;Rahman and Mishra, 2020) and vulnerability to food insecurity (Imai et al, 2015;Zereyesus et al, 2017;Bui and Hoang, 2020).…”
Section: Non-farm Participation and Food Expendituressupporting
confidence: 83%
“…Bezu et al (2012); Scharf and Rahut (2014) have also found that non-farm employment increases household expenditure in rural Ethiopia. These results also indirectly support empirical findings on the impact of non-farm employment on food security (Babatunde and Qaim, 2010;Imai et al, 2015;Tsiboe et al, 2016;Dzanku, 2019;Rahman and Mishra, 2020) and vulnerability to food insecurity (Imai et al, 2015;Zereyesus et al, 2017;Bui and Hoang, 2020).…”
Section: Non-farm Participation and Food Expendituressupporting
confidence: 83%
“…Adams (1994) and De Janvry and Sadoulet (2001) argue that participation in off‐farm employment reduces rural poverty by equalising income distribution and reducing household income inequalities in rural communities. This has a positive net effect on food security and nutrition, particularly for households living in areas with low agro‐ecological potential (Rahman & Mishra, 2020; Zereyesus et al, 2017). Households with access to non‐farm income are less prone to the low prevalence of stunting, underweight and wasting among children in areas with high levels of food insecurity (Babatunde & Qaim, 2010).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Association between market access and HHDS for 324 smallholder householdsRahman and Mishra 2020;Sibhatu et al 2015; …”
mentioning
confidence: 99%